The Role of Environmental Drivers in Humpback Whale Distribution, Movement and Behavior: A Review - Meynecke, Jan-Olaf; de Bie, Jasper; Barraqueta, Jan-Lukas Menzel; Seyboth, Elisa; Dey, Subhra Prakash; Lee, Serena B.; Samanta, Saumik; Vichi, Marcello; Findlay, Ken; Roychoudhury, Alakendra; Mackey, Brendan (Frontiers in Marine Science, 2021)
Humpback whales, Megaptera novaeangliae, are a highly migratory species exposed to a wide range of environmental factors during their lifetime. The spatial and temporal characteristics of such factors play a significant role in determining suitable habitats for breeding, feeding and resting. The existing studies of the relationship between oceanic conditions and humpback whale ecology provide the basis for understanding impacts on this species. Here we have determined the most relevant environmental drivers identified in peer-reviewed literature published over the last four decades, and assessed the methods used to identify relationships. A total of 148 studies were extracted through an online literature search. These studies used a combined estimated 105,000 humpback whale observations over 1,216 accumulated study years investigating the relationship between humpback whales and environmental drivers in both Northern and Southern Hemispheres. Studies focusing on humpback whales in feeding areas found preferences for areas of upwelling, high chlorophyll-a concentration and frontal areas with changes in temperature, depth and currents, where prey can be found in high concentration. Preferred calving grounds were identified as shallow, warm and with slow water movement to aid the survival of calves. The few studies of migration routes have found preferences for shallow waters close to shorelines with moderate temperature and chlorophyll-a concentration. Extracting information and understanding the influence of key drivers of humpback whale behavioral modes are important for conservation, particularly in regard to expected changes of environmental conditions under climate change.